2019
DOI: 10.1002/ese3.476
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyclic wetting‐drying on the mechanical strength characteristics of coal samples: A laboratory‐scale study

Abstract: Water‐coal interactions have gained much recent attention, although few studies focus on the strength of coal under wetting‐drying cycles. This study investigates changes in the microstructure and mechanical strength of coal that are induced by water‐coal interactions, at the macroscale and microscale. Fourteen specimens after continuous wetting and fourteen specimens after wetting‐drying cycles were tested, indicating that peak stress and elastic modulus decrease with increasing continuous wetting time and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 67 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…The strength properties of rocks would be significantly deteriorated after the cyclic dry-wet treatment. Khanlari et al [22], Özbek [21], Zhao et al [32], Huang et al [40], and Chen et al [41] performed static compression tests after dry and wet cycles on sandstone, melted limestone, mudstone, and coalstone, respectively. All of the results shown that with the increase of the number of dry and wet cycles, the uniaxial compressive strength and triaxial compressive strength of the rock sample decreased to varying degrees.…”
Section: Geofluidsmentioning
confidence: 99%
“…The strength properties of rocks would be significantly deteriorated after the cyclic dry-wet treatment. Khanlari et al [22], Özbek [21], Zhao et al [32], Huang et al [40], and Chen et al [41] performed static compression tests after dry and wet cycles on sandstone, melted limestone, mudstone, and coalstone, respectively. All of the results shown that with the increase of the number of dry and wet cycles, the uniaxial compressive strength and triaxial compressive strength of the rock sample decreased to varying degrees.…”
Section: Geofluidsmentioning
confidence: 99%
“…Talapatra et al (2020) revealed the evolution law of coal deformation and strain and described the influence of moisture content on the permeability of coal through porous media in wet reservoir [26]. studied the influence of water-coal interaction on the mechanical strength of coal [27]. The results showed that with the increase of continuous wetting time and the number of dry and wet cycles, the peak stress and elastic modulus decreased and the peak strain increased.…”
Section: Introductionmentioning
confidence: 99%
“…e subsurface works in the western part of China is not only affected by the low temperature environment and freezethaw cycles but also influenced by factors such as acid rain and groundwater erosion. Not only hydrochemical reaction causes elements to redistribute between rocks and water [1], the volume expansion of water in the pores will also produce freezing force during the freeze-thaw cycles [2,3]. e freezing force leads to the expansion of the original defect and the generation and expansion of new cracks, which cause imbalances within its soil particles, water molecules, and ions and decrease in strength and increase in compressibility.…”
Section: Introductionmentioning
confidence: 99%